2020
DOI: 10.21203/rs.3.rs-31183/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurological Involvement of Coronavirus Disease 2019: A Systematic Review

Abstract: Background: In December 2019, unexplained cases of pneumonia emerged in Wuhan, China, which were found to be secondary to the novel coronavirus SARS-CoV-2. On March 11, 2020, the WHO declared the Coronavirus Disease 2019 (COVID-2019) outbreak, a pandemic. Although the most common presentations of COVID-19 are fever, cough and shortness of breath, several clinical observations indicate that COVID-19 does affect the central and peripheral nervous system. Methods: We conducted a systematic literature search from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 23 publications
1
30
0
8
Order By: Relevance
“…7 A systematic review conducted by Ghannam et al showed that 23% of the patients also had complications of encephalopathy or encephalitis. 8 The results of both studies indicated the possibility of central nervous system involvement in the course of COVID-19 disease, with the presence of SARS-CoV-2 neurotropism. 9 Previous studies have reported cases of encephalitis related to COVID-19, with varying clinical appearance, laboratorial and imaging ndings.…”
mentioning
confidence: 92%
“…7 A systematic review conducted by Ghannam et al showed that 23% of the patients also had complications of encephalopathy or encephalitis. 8 The results of both studies indicated the possibility of central nervous system involvement in the course of COVID-19 disease, with the presence of SARS-CoV-2 neurotropism. 9 Previous studies have reported cases of encephalitis related to COVID-19, with varying clinical appearance, laboratorial and imaging ndings.…”
mentioning
confidence: 92%
“…Secondly, the characteristic pattern of stroke in individuals with COVID-19, with an increased proportion of large artery occlusion, infarction involving multiple territories, and increased cryptogenic aetiology, suggests a causal relationship in at least a proportion of patients.Previous reports have been published with the attempt to clarify the relationship between stroke and COVID-19. These included narrative reviews(32,33), systematic reviews(9)(10)(11)34) and metaanalyses(34,35). While some authors have focused on the relationship between personal history of CVD and COVID-19(7, 8), we studied the incidence and risk factors for the occurrence of new CVD in concomitant SARS-CoV2 infection, searching for a specific profile of COVID-19associated stroke.…”
mentioning
confidence: 99%
“…The SARS-CoV-2 infection is not only a respiratory disease; neurological involvement is not rare. This has been clear from the first analysis of 214 cases of COVID-19 in Wuhan (China), where 36.4% (78) patients presented with neurological complications 19 .…”
Section: Discussionmentioning
confidence: 98%